The updated ASCO/CAP guideline recommendations for HER2 testing in the management of invasive breast cancer: a critical review of their implications for routine practice. Issue 5 (31st January 2014) - Rakha, Emad A; Starczynski, Jane; Lee, Andrew H S; Ellis, Ian O
<x xml:space="preserve">Abstract</x> The American Society of Clinical Oncology and the College of American Pathologists have issued joint updated comprehensive guideline recommendations for human epidermal growth factor receptor 2 (HER2) testing in breast cancer. The update not only provides guidelines for the test performance parameters, with the aim of improving test accuracy, reproducibility, and precision, but also provides comprehensive recommendations on the post‐analytical interpretation of the results, and requires improved communication among healthcare providers. The updated guidelines are targeted at testing laboratories, pathologists, oncologists, surgeons, and, indirectly, other healthcare providers. Although the guidelines contribute to the improved analytical validity and clinical utility of laboratory assays required for successful molecularly targeted therapy in the era of personalized medicine, the implications of such recommendations have to be acknowledged. Certain recommendations, particularly those related to repeating the test and pathological concordance, have lower levels of supportive evidence than existing key recommendations, and the associated workload implications will be challenging to support in most healthcare systems. In this commentary, we critically address the key updated recommendations and their impact on service provision and patient care.